2020
DOI: 10.18805/ijare.a-540
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between Mitochondrial and Nuclear DNA Genes Suggests the Possibility of Hybridization of Indian and Southeast Asian Types of Oecophylla smaragdina (Fabricius) (Hymenoptera, Formicidae) in Bangladesh

Abstract: Background: Oecophylla smaragdina is distributed from India, SE Asia and Australia including many tropical Islands. A recent phylogenetic study based on mitochondrial DNA analysis reveals that Bangladesh is the overlapping zone of both Indian and Southeast Asian type of O. smaragdina. These two different lineages of Indian and SE Asian type have the opportunities of creating the zone of contacts, but no such data was found. In this study, shed light was given to reveal the chance of hybridized colony of O. sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In the case, where mtDNA are SE Asian type, the crossing might to be expected between the male of Indian type and female of SE Asian type and mtDNA are maternally inherited. Through, comparing the results of the nucleotide sequences obtained from nDNA analysis by LW Rh and mtDNA and nDNA inconsistency was observed (Rahman et al 2020) and it partially reveals the hybrid phenomenon but cannot fully detect the hybridization status of the colony. In addition, in the diploid cell, the nucleus can contain both the Indian and SE Asian types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case, where mtDNA are SE Asian type, the crossing might to be expected between the male of Indian type and female of SE Asian type and mtDNA are maternally inherited. Through, comparing the results of the nucleotide sequences obtained from nDNA analysis by LW Rh and mtDNA and nDNA inconsistency was observed (Rahman et al 2020) and it partially reveals the hybrid phenomenon but cannot fully detect the hybridization status of the colony. In addition, in the diploid cell, the nucleus can contain both the Indian and SE Asian types.…”
Section: Introductionmentioning
confidence: 99%
“…Azuma et al (2006) through long wavelength rhodopsin (LWRh) analysis categorized the Indian and SE Asian type of O. smaragdina population as Smaragdina B and Smaragdina A and suggested that SE Asian are derived and monophyletic while the Indian type is the ancestral. Discordant genetic 1 Detection of Heterozygosity and Allelic Frequency of Indian and Southeast Asian Types of Oecophylla smaragdina (Fabricius)... relationships usually occurred from mitochondrial introgression or the incomplete lineage sorting (Eto et al 2013) which was observed from the two types of weaver ants in Bangladesh (Rahman et al 2020). The occured discordancy can partially reveal the hybrid phenomenon but cannot fully detect the hybridization status of the colony by revealing the identical alleles.…”
Section: Introductionmentioning
confidence: 99%